“Il Grande Spettacolo”: Oriana Fallaci e la narrazione alla New Journalism sul programma spaziale americano - Tichoniuk-Wawrowicz, Ewa (Romanica Silesiana, 2020)
Oriana Fallaci had the opportunity to closely observe the efforts the US made during the Space Race which was sealed in 1957 by the launch of the first Russian Sputnik. The journalist knew dozens of NASA workers (including astronauts, engineers and doctors) and others (external scientists, advertisers, writers). Based on the interviews and articles printed in L’Europeo, Fallaci published two books Se il Sole muore (1965) and Quel giorno sulla Luna (1970). Recently, the publishing house Rizzoli collected some of Fallaci’s texts that appeared in this weekly newspaper (L’Europeo) between 1964 and 1980 in the volume La Luna di Oriana (2018). It would be worth analyzing the cornerstones of Fallaci’s narrative approach, resembling in many ways the American New Journalism – with its tension between information and emotion, interpretation and persuasion – in her work before the famous war reports.